"You're all going to hate the word 'recovery' by the end of this": Service users' views of measuring addiction recovery. (February 2015) - Neale, Joanne; Tompkins, Charlotte; Wheeler, Carly; Finch, Emily; Marsden, John; Mitcheson, Luke; Rose, Diana; Wykes, Til; Strang, John
Abstract Aims: To explore how service users' views of measuring addiction recovery differ from those of service providers. Methods: Five focus groups conducted in two English cities with (i) people currently using Class A drugs (n = 6); (ii) people currently using alcohol (n = 12); (iii) individuals in residential detoxification (n = 12); (iv) individuals in residential rehabilitation (n = 7); and (v) people who defined themselves as ex drug or alcohol users (n = 7). Each focus group reviewed 76 measures of recovery previously identified by senior service providers. Findings: Service users identified multiple problems with the 76 measures. Difficulties could be categorized as expecting the impossible of service users; the dangers of progress; the hidden benefits of negative outcomes; outcomes that negate the agency in recovery; contradictory measures; failure to recognise individual differences; entrenched vulnerabilities; the misattribution of feelings and behaviours; and inappropriate language. Conclusions: Service users experience recovery as a process and personal journey that is often more about 'coping' than 'cure'. Involving service users in designing measures of recovery can lessen the likelihood that researchers develop assessment tools that use inappropriate, contradictory or objectionable outcomes, and ambiguous and unclear language. People who have experienced drug or alcohol problems can highlight important weaknesses in dominant recovery discourses.